(untitled) (Research, Society and Development, 2021)
The coronavirus pandemic (SARS-CoV-2) significantly impacted health systems and challenged the multidisciplinary team, which is considered a global public health problem. Several strategies have been suggested aiming at safety and minimizing the exposure of health professionals and hospitalized patients to the virus, one of which is to avoid procedures that generate aerosols during surgical procedures, such as airway management. Therefore, regional and local anesthesia has become a viable, effective and safe alternative to general anesthesia, playing an important role during the outbreak of COVID-19, when applicable. Among the advantages, one can mention the non-generation of aerosols, postoperative analgesia, reduction of nausea and vomiting, as well as cardiorespiratory complications. This study aims to investigate the application of regional anesthesia in different medical specialties during the coronavirus pandemic, evaluating the results of its use. A search was performed in Pubmed, Web of Science (all databases), Scopus, Embase, and Cochrane Library databases using the search terms “SARS-CoV-2”, “COVID-19”, “Anesthesia, Local” and “Anesthetics, Local” where 49 references were included. Studies show good results in the techniques used and enable a safe alternative treatment in various surgical fields. Thus, regional and local anesthesia are suitable and viable for medical surgical procedures and constitute a good alternative to general anesthesia and can be applied in different surgical specialties.